The Electromagnetic Transients in Compensated High Voltage Power Lines - Mohamed M. Saied (International Journal of Electrical Power and Machine Systems, 2024)
This paper addresses the simulation of the transients developed in high voltage lines, which are initiated by lightning discharges. The analysis allows for compensated and uncompensated lines. Both the individual and simultaneous series inductive and shunt capacitive compensation types can be dealt with. The sizes and locations of the compensating elements are included in the analysis. Numerous studies on the transient concentrated stresses across these elements and the related protection concerns have been carried out in recent years. With the use of sophisticated computer programs, like the well-known Electromagnetic Transient Program (EMTP), it is possible to assess and mitigate eventually excessive transient voltages and currents by using high power varistors and arresters. The derived mathematical model includes simultaneous partial differential equations governing the current and voltage along the line as functions of the location and time subject to appropriate initial and boundary conditions. A Mathematica approach is adopted in order to get the current and voltage in the Laplace s-domain followed by their numerical inversion to the time-domain. The model and computer code are validated via discussing the results of special cases of known exact solutions.
Keywords: Compensation; Simulation; differential equations; electromagnetic; high voltage lines; mathematica; numerical laplace inversion; parallel; series; towers; transients